Proceedings of the international conference on IT convergence and security 2011 - Kim, Kuinam J. (Lecture notes in electrical engineering, 2012)
As we entered the 21st century, the rapid growth of information technology has changed our lives more conveniently than we have ever speculated. Recently in all fields of the industry, heterogeneous technologies have converged with information technology resulting in a new paradigm, information technology convergence. In the process of information technology convergence, the latest issues in the structure of data, system, network, and infrastructure have become the most challenging task. Proceedings of the International Conference on IT Convergence and Security 2011 approaches the subject matter with problems in technical convergence and convergences of security technology by looking at new issues that arise from techniques converging. The general scope is convergence security and the latest information technology with the following most important features and benefits: 1.      Introduction of the most recent information technology and its related ideas 2.      Applications and problems related to technology convergence, and its case studies 3.      Introduction of converging existing security techniques through convergence security Overall, after reading Proceedings of the International Conference on IT Convergence and Security 2011, readers will understand the most state of the art information strategies and technologies of convergence security. Part 1 Security fundamentals -- Part 2 Industrial & business information security -- Part 3 Security protocols and applications -- Part 4 Convergence security -- Part 5 IT Convergence applications -- Part 6 Mobile computing and future networks -- Part 7 Multimedia and information visualization -- Part 8 Web technology and software engineering.